DAMPAK RELOKASI TERHADAP LINGKUNGAN SOSIAL PEDAGANG KAKI LIMA DI PUSAT KULINER PRATISTHA HARSA PURWOKERTO - Rochmat Aldy Purnomo (Universitas Muhammadiyah Ponorogo, 2016)
This study aimed to analyze aspects of the social environment of street vendors between before and after relocating to Pratistha Harsa. Collecting data using the techniques of interview, observation and literature. The respondents were selected is Pratistha Harsa Chief Manager, Chairman of the Society Pratistha Harsha, traders culinary Pratistha Harsa. The population of merchants who relocated to Pratistha Harsa number of 65 traders and a sample of 40 traders. Selection of the sample using simple random sampling. This study uses Wilxocon analysis test. The results showed that an increase in the average of the perception of traders about the safety, cleanliness, lighting and ease of relocation time before and after the relocation.This study aimed to analyze aspects of the social environment of street vendorsbetween before and after relocating to Pratistha Harsa. Collecting data using thetechniques of interview, observation and literature. The respondents were selectedis Pratistha Harsa Chief Manager, Chairman of the Society Pratistha Harsha, tradersculinary Pratistha Harsa. The population of merchants who relocated to PratisthaHarsa number of 65 traders and a sample of 40 traders. Selection of the sampleusing simple random sampling. This study uses Wilxocon analysis test. The resultsshowed that an increase in the average of the perception of traders about the safety,cleanliness, lighting and ease of relocation time before and after the relocation.